A.S.P.E.N. Clinical Guidelines: Nutrition Support of Neonatal Patients at Risk for Metabolic Bone Disease. Issue 5 (17th May 2013) - Nehra, Deepika; Carlson, Sarah J.; Fallon, Erica M.; Kalish, Brian; Potemkin, Alexis K.; Gura, Kathleen M.; Simpser, Edwin; Compher, Charlene; Puder, Mark; ,
Abstract : Background : Premature infants are at increased risk for metabolic bone disease, with resulting delayed bone growth, osteopenia, and rickets. Method : A systematic review of the best available evidence to answer a series of questions regarding neonatal patients at risk of metabolic bone disease receiving parenteral or enteral nutrition was undertaken and evaluated using concepts adopted from the Grading of Recommendations, Assessment, Development and Evaluation working group. A consensus process was used to develop the clinical guideline recommendations prior to external and internal review and approval by the American Society for Parenteral and Enteral Nutrition Board of Directors. Questions : (1) What maternal risk factors predispose the neonate to metabolic bone disease? (2) What is the optimal type of feeding to promote neonatal bone health? (3) When and how should vitamin D supplements be administered? (4) Does parenteral nutrition (PN) predispose a neonate to metabolic bone disease, and if so, are there PN formulation recommendations to minimize this risk?